2020
DOI: 10.1002/jha2.4
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, placebo‐controlled, phase 3 study of perifosine combined with bortezomib and dexamethasone in patients with relapsed, refractory multiple myeloma previously treated with bortezomib

Abstract: Perifosine, an investigational, oral, synthetic alkylphospholipid, inhibits signal transduction pathways of relevance in multiple myeloma (MM) including PI3K/Akt. Perifosine demonstrated anti‐MM activity in preclinical studies and encouraging early‐phase clinical activity in combination with bortezomib. A randomized, double‐blind, placebo‐controlled phase 3 study was conducted to evaluate addition of perifosine to bortezomib‐dexamethasone in MM patients with one to four prior therapies who had relapsed followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…A phase I study of perifosine, lenalidomide, and dexamethasone in RRMM produced an encouraging 73% ORR and found that responders had higher baseline bone marrow phospho-Akt levels, identifying another potential biomarker for agents targeting the PI3K/AKT pathway ( 44 ). A more recent phase III study, however, randomized patients to bortezomib and dexamethasone with or without perifosine but found no signal towards improved response rates or progression-free survival (PFS) at the first interim analysis and was discontinued ( 45 ). The pan-Akt inhibitor afuresertib has also been clinically tested in multiple myeloma, with initial monotherapy trials discontinued due to limited single agent activity ( 46 ).…”
Section: Previous Clinical Pursuits: Targeted Approaches Show Mixed Clinical Resultsmentioning
confidence: 99%
“…A phase I study of perifosine, lenalidomide, and dexamethasone in RRMM produced an encouraging 73% ORR and found that responders had higher baseline bone marrow phospho-Akt levels, identifying another potential biomarker for agents targeting the PI3K/AKT pathway ( 44 ). A more recent phase III study, however, randomized patients to bortezomib and dexamethasone with or without perifosine but found no signal towards improved response rates or progression-free survival (PFS) at the first interim analysis and was discontinued ( 45 ). The pan-Akt inhibitor afuresertib has also been clinically tested in multiple myeloma, with initial monotherapy trials discontinued due to limited single agent activity ( 46 ).…”
Section: Previous Clinical Pursuits: Targeted Approaches Show Mixed Clinical Resultsmentioning
confidence: 99%
“…A few clinical trials have assessed the efficacy of perifosine, an AKT-inhibitor, as monotherapy or in combination regimens with mixed results [84,85], while a phase III trial that evaluated the combination of perifosine with bortezomib and dexamethasone was stopped at the interim analysis due to lack of efficacy in terms of ORR and PFS in the perifosine arm compared to the placebo arm [86].…”
Section: Pi3k/akt Pathway Directed Therapiesmentioning
confidence: 99%
“…Another phase I/II-trial testing perifosine in combination with bortezomib and dexamethasone showed a response rate (≥minor remission (MR)) of 41% in patients relapsed or refractory to bortezomib, however, with a PFS of only 6.8 months [ 80 ]. A phase III trial (ClinicalTrials.gov Identifier: NCT01002248) further evaluating this combination was stopped at the first interim analysis due to a lack of benefit in responses (ORR ≥ PR 20% vs. 27 %) and PFS (22.7 weeks (95% CI 16.0–45.4) in the perifosine arm and 39.0 weeks (18.3–50.1) in the placebo arm) [ 81 ].…”
Section: Pi3k/akt-pathway-directed Therapiesmentioning
confidence: 99%